On Ovid's Metamorphoses - Williams, Gareth (Columbia University Press, 2023)
Drawing on many years of teaching Ovid's Metamorphoses, Gareth Williams offers a brisk and lively reading of the poem that emphasizes why it speaks in compelling ways to a twenty-first-century audience. He shows how the Metamorphoses is not just a colorful collection of stories about change but an exploration of change itself. Intro – Table of Contents – Preface – Introduction – 1. Diversity, Idiosyncrasy, and Self-Discovery in the Metamorphoses – 2.The Liabilities of Language: Change and Instability in Ovid's World of Words – 3. The Path of Deviance: Sexual Morality and the Incestuous Urge in the Metamorphoses – 4. Rough Justice: Victimization, Revenge, and Divine Punishment in the Metamorphoses – Epilogue – Further Reading – Index.
Description based on publisher supplied metadata and other sources
Keywords: Change in literature; Fables; Latin-History and criticism; Latin poetry-History and criticism; Electronic books